Avaliação morfofuncional dos músculos do quadril e joelho, e perfil psicológico de pessoas com disfunções femoropatelares - Siqueira, Malu dos Santos (2023)
Patellofemoral pain (PFP) and patellofemoral osteoarthritis (PFOA) are highly prevalent musculoskeletal disorders, being present in approximately 23% of the general population and 39% of people aged ≥ 30 years, respectively. They are characterized by pain in the anterior region of the knee and have a poor prognosis in most cases, with 50% of patients with PFP reporting persistent pain and/or progression to PFOA, and 31% of patients with PFOA progressing to worsening of the condition and/or development of tibiofemoral osteoarthritis. The increased overload of the patellofemoral joint and consequent worsening of the condition, is potentiated by biomechanical changes such as increased hip internal rotation and hip adduction, and weakness of the abductor, lateral rotator and extensor muscles of the hip and quadriceps. In the PFOA, little has been investigated about the strength level of the hip and knee muscles, and the studies that investigated the effect of strengthening these muscle groups showed contradictory results regarding the effects durability. hus, there is still no consensus on whether or not these people have weakness in this muscle and how much they could benefit from strengthening targeted at these muscle groups. Thus, for a specific treatment to be developed for the needs of these patients, it is necessary to be sure which muscles are affected in this condition. In PFP, despite the fact that studies have actually observed weakness in the hip and quadriceps muscles of these patients, and muscle strengthening has shown positive results in improving pain and functionality, the prognosis of half of these patients is unfavorable after 5 to 8 years. Thus, in addition to biomechanical changes, studies have also investigated whether there is any psychological condition installed in these patients, since worst psychological condition could negatively influence their prognosis. However, few studies have been carried out and there is no consensus about the subject. Thus, based on these gaps in the literature, this thesis aimed to investigate whether people with PFOA have worse strength, volume and/or activation of the hip and quadriceps muscles than pain-free people, and; to investigate whether people with PFP have worst psychological condition than pain-free people, so that specific therapies for mental disorders can be included in the treatment of these patients. Thus, manuscript 1 of this thesis was a systematic review and meta-analysis of studies that compared the strength, volume or activation of the hip and quadriceps muscles between people with PFOA and pain-free controls. As a result, meta-analyses have proven that people with PFOA have less strength in the hip abductor, lateral rotators and extensors and quadríceps muscles, and the analysis of individual studies has shown less muscle volume in the gluteus medius, gluteus minimus, tensor fasciae latae, vastus medialis, vastus lateralis, and rectus femoris, as well as changes in activation of the VL, VM, and gluteus maximus muscles in people with PFOA when compared to asymptomatic controls. The certainty of evidence was very low, mainly due to imprecision and indirectness according to the Grading of Recommendations Assessment, Development and Evaluation (GRADE). In the second manuscript of this thesis, also in a systematic review with meta-analysis, studies that investigated emotional reactions, anxiety, depression, kinesiophobia and pain catastrophizing of people with PFP were compared to pain-free controls were compared. Meta-analyses have shown that people with PFP present with emotional reactions, kinesiophobia and pain catastrophizing significantly worse than their pain-free controls. Only 1 study investigated anxiety and depression in isolation, and this one did not observe a significant difference. Despite the concrete results of this review, the level of evidence for all outcomes was very low according to GRADE.